ANALISIS PELAKSANAAN SISTEM MANAJEMEN MUTU BERBASIS INTERNATIONAL ORGANIZATION FOR STANDARDIZATION (ISO) 9001:2008 DI SMK NEGERI 3 JAYAPURA - Martza; Tanta; Kusdianto (Jurnal Penjaminan Mutu, 2023)
The research objectives are to analyze the implementation of (1) Procedur Management System; (2) Management responsibilities; (3) Resource management; and (4) Supporting and constraining factors of quality management system based on ISO 9001:2008. This type of research is descriptive qualitative with a case study approach. This research was conducted at SMK Negeri 3 Jayapura. Sources of data in this study were the Principal, Deputy Quality Management, Head of Administration, Deputy Head of Curriculum, Deputy Head of Public Relations, Deputy Head of Student Affairs, Head of Department, Teachers, Supervisors, and Committees. The research instrument is the researcher himself, interview guidelines, observation guidelines, and documentation guidelines. The data analysis technique is qualitative data analysis following the concept of Miles and Huberman (1992), including data reduction, data display, and verification/conclusion. The data validity technique uses data triangulation. The results showed that (1) the procedure management system was successfully implemented. The achievement can see this of the school's quality targets classified as successful. (2) Management responsibility has been successfully implemented. This can be seen from the management commitment, focus on customers, quality policy and responsibility, and communication is carried out by conducting periodic internal and external quality audits; (3) Resource management at SMK Negeri 3 Jayapura is classified as successful, this can be seen in the supporting physical resources, supporting human resources, complete infrastructure, and a comfortable working environment; (4) Factors supporting was successfully implemented, namely: a) Commitment and Awareness of all School Citizens, b) Quality of Human Resources, c) Adequate Infrastructure.